Antidepressant use and stroke or mortality risk in the elderly. (25th October 2021) - Ön, Begüm Irmak; Vidal, Xavier; Berger, Ursula; Sabaté, Mònica; Ballarín, Elena; Maisterra, Olga; San‐Jose, Antonio; Ibáñez, Luisa
Abstract: Background and purpose: Current evidence on antidepressant‐related stroke or mortality risk is inconsistent. Because the elderly have the highest exposure to antidepressants, the aim was to quantify their association with stroke and mortality risks in this vulnerable population. Methods: Persons over 65 years old and registered in the Information System for Research in Primary Care of Catalonia during 2010–2015 comprised the study population. Antidepressant exposure was categorized into current‐users, recent‐users, past‐users and antidepressant non‐users (controls). The effect of antidepressant exposure on stroke or death, whichever came first, was analyzed by Cox regression adjusted for established risk factors. Results: Of the 1, 068, 117 participants included, 20% had antidepressant reimbursements during follow‐up, 17% had a stroke and 3% died. The risk of experiencing stroke or death was higher in antidepressant current‐users (hazard ratio [HR] 1.04; 95% confidence interval [CI] 1.02–1.06), recent‐users (HR 3.34; 95% CI 3.27–3.41) and past‐users (HR 2.06; 95% CI 2.02–2.10) compared to antidepressant non‐users. Antidepressant current‐use was associated with increased stroke (HR 1.56; 95% CI 1.50–1.61) but decreased mortality risk (HR 0.93; 95% CI 0.91–0.94). During antidepressant recent‐use and past‐use, both stroke and mortality risks were significantly increased compared to no antidepressant use. Conclusions: Antidepressant use may be associated with increased stroke risk in the elderly. When using antidepressants in this population, the potential risks should be considered. Abstract : In real‐world data of the elderly population, it was found that the risk of experiencing stroke or death in antidepressant users during and up to 1 year after exposure was higher compared to non‐users, even after adjustment for possible confounders.